ORGANIZATIONAL CULTURE OF THE INDONESIAN AIRPORT MANAGEMENT COMPANY : A CASE STUDY AT PT. ANGKASA PURA I - Edward Efendi Silalahi (International Journal of Social Science, 2023)
The study aim at analyzing the organizational culture structuring seen from the perspective of 7s Mc Kinsey and analyzing the organizational culture contributions against crucial success factors on the company's financial performance aspect. Qualitative research use with the case study approach at PT Angkasa Pura I as a commercial transport management company, which is one of the Indonesian states - owned enterprises. Desain explorative and descriptive use complement this research. Data collection do through observation, interviews, literature study, and focus group discussion. Data analysis doing by a successive approximation technique. The results showed that seven components include structure, systems, style, staff, skill, strategy, and shared value/superordinate goals in the organization's effects and influenced by the culture of the organization, so the setup or repair of system components will affect the organizational culture. Similarly, the setup or improvement of the cultural organization will affect the organizational system components. Also, research results show that the development of organizational culture and on going socialization affects the growth of profitability (ROA, ROE).